2018
DOI: 10.1108/he-05-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perspectives of a new food literacy curriculum in Australia

Abstract: Purpose Implementation of a new food literacy curriculum provides multiple health and social benefits to school students. The success of any new curriculum execution is partly determined by teachers’ perceptions about the new curriculum contents, and barriers and challenges for its delivery. The purpose of this paper is to explore teachers’ views of a new food literacy curriculum named Victorian Certificate of Education Food Studies for senior secondary school students in Victoria, Australia. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 40 publications
(56 reference statements)
2
20
0
2
Order By: Relevance
“…Regarding the debate on the topic of environmental sustainability, the authors of seven papers that explored FL discussed the issue [3,12,16,24,65,71,78]. From their observations, we noted that FL implies the development of critical thinking as well as awareness of the connection between the food that is consumed and the environment.…”
Section: Comparison Between Nl and Fl Consequencesmentioning
confidence: 98%
See 1 more Smart Citation
“…Regarding the debate on the topic of environmental sustainability, the authors of seven papers that explored FL discussed the issue [3,12,16,24,65,71,78]. From their observations, we noted that FL implies the development of critical thinking as well as awareness of the connection between the food that is consumed and the environment.…”
Section: Comparison Between Nl and Fl Consequencesmentioning
confidence: 98%
“…The authors of three papers pointed out that NL gave rise to skilled individuals [22,29,30], since the authors of other eight papers conceptualized NL as a skill-based process that led individuals to make healthy food choices and develop healthy dietary habits [22,35,[45][46][47]49,51,54]. Analogously, twelve papers that discussed FL agreed that this dimension implied improved food and nutrition knowledge, and skills such as cooking [16,21,23,37,56,61,62,65,[70][71][72][73]. The authors of twenty-three papers also stated that the achievement of FL leads to a healthy diet, better food and physical activity choices, and healthy behaviors (i.e., eat more vegetables or fruits, consume less soda and sweetened beverages, engage in more physical activity, increase spice use and decrease salt use, decrease serving sizes including fast food, reduce frequency of consumption of packaged and processed snacks, increase purchasing of fresh foods, and increase use of food labels when selecting foods) [3,10,11,16,[20][21][22][23][24]39,40,42,56,57,59,61,62,67,…”
Section: Comparison Between Nl and Fl Consequencesmentioning
confidence: 99%
“…The continuous professional development (CPD) is described as an "important professional life investment" or "renewal/refreshment" (Day, Sammons, Stobart, Kington, & Gu, 2007). Implementation of a new food literacy curriculum provides multiple health and social benefits to school students (Nanayakkara, Margerison, & Worsley, 2018). The teachers' perceptions about the new curriculum contents, barriers and challenges in delivering, are basically for the success of its implementation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exploration of teachers’ opinions regarding food literacy education is important to identify their resource needs and the challenges they face in curriculum delivery. Accordingly, the authors explored food system professionals’ and teachers’ opinions of these two topics using qualitative studies and the results have been reported previously [ 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of these qualitative studies [ 40 , 41 , 42 ] were used to design a quantitative survey of food professionals’ and teachers’ opinions of these two areas. The specific objectives of this study were to explore these professionals’: (i) opinions of the importance of food literacy education for senior secondary school students, (ii) support for the inclusion of different food-related topics in the senior secondary school food literacy curriculum, (iii) views of the importance of students’ food literacy-related activities and assessment tasks, (iv) perceptions of barriers and challenges for delivering food literacy education to senior secondary school students, and (v) suggestions for improving the quality and relevance of senior secondary school food literacy education.…”
Section: Introductionmentioning
confidence: 99%